Freedom on the menu : the Greensboro sit-ins - Weatherford, Carole Boston, 1956-; Lagarrigue, Jerome (New York : Dial Books for Young Readers, 2005)
The 1960 civil rights sit-ins at the Woolworth's lunch counter in Greensboro, North Carolina, are seen through the eyes of a young Southern black girl.
Keywords: African Americans -- North Carolina -- Greensboro -- Juvenile fiction; African Americans -- Fiction; Civil rights demonstrations -- Fiction; Greensboro (N.C.) -- Race relations -- Fiction